Analysis of the adequacy of the finite element model of sintering process of the iron ore charge - Мных, Антон Сергеевич; Пазюк, Михаил Юрьевич; Мных, Ирина Николаевна (Technology audit and production reserves, 2015)
The analysis of the current state of the problem of modeling the sintering process is conducted and weaknesses in existing numerical models are identified. The simulation results of the sintering process burden on the author’s developed finite element thermal model of the sintering process, taking into account segregation processes in the layer of feed material, namely the distribution of fuel and chemical compounds by height of layer. The results of simulation and field experiment conducted in the experimental device of sinter plant IC "Zaporizhstal" (Ukraine) are analyzed for the sintering conditions on the existing sinter machine № 1, confirmed the adequacy of the presented model. Simulation error is 2,61 % that indicates the possibility of using this model to conduct numerical experiments to manage segregation of charge materials and fuel in order to optimize the thermal regime of the sintering process.